1997
DOI: 10.1200/jco.1997.15.4.1529
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of renal cell carcinoma with iodine-131-labeled chimeric monoclonal antibody G250.

Abstract: PURPOSE Pharmacokinetics, biodistribution, immunogenicity, and imaging characteristics of iodine 131 (131I)-labeled chimeric monoclonal antibody (mAb) G250 (cG250) were studied in patients with renal cell carcinoma (RCC) to determine the therapeutic potential of this antibody. PATIENTS AND METHODS Sixteen patients with RCC received a single intravenous (IV) infusion of 6 mCi 131I-labeled cG250. Five protein dose levels were investigated (2 to 50 mg). Planar scintigraphic images were acquired, and normal tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
138
0
3

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(150 citation statements)
references
References 10 publications
9
138
0
3
Order By: Relevance
“…17 The extensive study of this mAb, including two phase I clinical trials, revealed no adverse reactions in the patients treated and showed that G250 mAb was concentrated in RCC tumors after intravenous injections. 18,19 These findings suggested that G250 TAA could be a suitable candidate for cell targeting and gene delivery. Indeed, due to the poor efficiency of conventional treatments, 32 the design of new strategies remains a major issue in the therapy of RCC.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…17 The extensive study of this mAb, including two phase I clinical trials, revealed no adverse reactions in the patients treated and showed that G250 mAb was concentrated in RCC tumors after intravenous injections. 18,19 These findings suggested that G250 TAA could be a suitable candidate for cell targeting and gene delivery. Indeed, due to the poor efficiency of conventional treatments, 32 the design of new strategies remains a major issue in the therapy of RCC.…”
Section: Discussionmentioning
confidence: 93%
“…Moreover, significant clinical experience has been obtained in two phase I studies with 131 I-labeled mAb G250 to evaluate toxicity, pharmacokinetics, and localization capabilities. 18,19 These studies have established the lack of cross-reactivity with normal tissues, with the exception of cells of the larger bile ducts and gastric mucosal cells.…”
mentioning
confidence: 97%
“…CA9 is a known antigen currently being targeted for RCC immunotherapy (Divgi et al, 1998;Steffens et al, 1999;Uemura et al, 1999;Grabmaier et al, 2000;Li et al, 2001;Bui et al, 2003;Kennett, 2003). To compare expression of CD70 with CA9, we performed real-time quantitative RT -PCR analysis on multiple normal tissues and clinical RCC samples (Figure 7).…”
Section: Cd70 Exhibits a More Restricted Normal Tissue Distribution Amentioning
confidence: 99%
“…An example of an antigen found to be overexpressed in RCC is carbonic anhydrase IX (CA9), which is the target for the monoclonal antibody (mAb) G250 (Pastorek et al, 1994;Uemura et al, 1999;Grabmaier et al, 2000;Li et al, 2001;Bui et al, 2003). Immunoscintigraphy of RCC patients dosed with iodine-131-labelled G250 demonstrated tumour targeting to metastatic sites (Divgi et al, 1998;Steffens et al, 1999;Kennett, 2003).…”
mentioning
confidence: 99%
“…48 -50 For a few murine antibodies, replacement of the C regions of the light and heavy chains by human C regions may not provide the solution to the problem of reducing HAMA responses in patients, because the V regions are potentially immunogenic and can lead to the development of antiidiotypic antibodies in patients. [47][48][49][50] Therefore, other approaches for reducing the immunogenicity of murine MAbs have been sought. The murine V regions can be genetically humanized by the grafting of CDRs into human framework regions.…”
Section: Analysis Of Immunogenicity Of Cc49 Scfvsmentioning
confidence: 99%